How to become a better reading teacher: Strategies for assessment and intervention - Lillian R Putnam (Merrill, 1996)
This book is intended to be useful to classroom teachers who work daily with children who have reading disabilities, as well as to preservice teachers as they prepare to enter the most rewarding profession there is